Традиційні цінності та практика співжиття населення Бишівської громади Київщини за умов воєнної агресії росії - Пономар, Л. (Матеріали до української етнології, 2023)
У статті розглядаються нові мотивації та нові суспільні орієнтації поведінки під час війни на прикладі практики співжиття населення Бишівської громади Київщини. Дослідження культури населення сіл цієї громади показало велике значення традиційної спадщини для збереження самобутності, зокрема, на прикладі свята Маковія у Веселій Слободі. Патріотична самосвідомість у дні війни згуртувала односельців на своєму «малому фронті», стала ключовою в самоорганізації, взаємодопомозі, Наголошено, що сучасні дослідження мають велике значення для збереженні пам’яті про війну росії проти України. Записи співжиття довоєнного часу та воєнного лихоліття фіксують зміни, які є важливим матеріалом для їх інтерпретації. Тому в статті широко використано записи від інформаторів. Мешканці сіл Бишівської громади роблять свій внесок в оборону рідної землі, займаються волонтерською діяльністю, стали частиною руху національного спротиву, демонструючи самовідданість, жертовність, незламність. В оповідях жителів сіл відображено перші емоційні переживання на початку війни, дії щодо швидкого згуртування, єдності та підтримки: взаємодопомога, звичаї сусідства односельців. В обороні сіл Яблунівка та Перевіз річка Ірпінь стала природною перешкодою на шляху ворогів до Києва, унеможливила їхнє просування. Розглянуто практики вшанування загиблих. У статті показано усвідомлення жителями сіл тяглості традицій від часів Київської Русі. На прикладі фестивалю «Купальське Коло» в селі Грузьке Фастівського району Київської області за підтримки Бишівської громади показано непересічне значення народної культури як «інформативного і духовного фронтів». New motivations and social orientations of behavior during the war, exemplified by the practice of coexistence of the population of the Byshiv community of Kyivshchyna, are considered in the article. The study of the culture of the population of the villages of this community has shown the great importance of traditional heritage for the preservation of originality, in particular, exemplified by the Honey Feast of the Saviour in Vesela Sloboda. Patriotic self-consciousness in the days of war has united the fellow villagers on their small front, becoming a key phenomenon in self-organization, mutual aid. It is emphasized that modern research is of great importance in preserving the memory of Russia’s war against Ukraine. Records of pre-war and wartime coexistence are evidence of changes that are important material for their interpretation. Therefore, the informants’ records are used widely in the article. Residents of the villages of Byshiv community contribute to the defense of their native land, are engaged in volunteer activities, and have become a part of the national resistance movement, demonstrating selflessness, sacrifice, and invincibility. The first emotional experiences at the beginning of the war, actions concerning the rapid rallying, unity, and support, namely mutual aid, neighbourhood customs of fellow villagers, are reflected in the stories of the inhabitants of the villages. The Irpin River has become a natural obstacle in the defense of the villages of Yablunivka and Pereviz, as well as on the enemies’ way to Kyiv, making their attacks impossible. The practices of commemorating the dead are considered. The awareness of the inhabitants of the villages of the persistence of traditions from the times of Kyivan Rus is described in the article. The unique importance of folk culture as the informative and spiritual fronts is exemplified by the Kupala Circle festival in the village of Hruzke of Fastiv district in Kyiv region, with the support of the Byshiv community.